Antibiotic consumption and utilization at a large tertiary care level hospital in Uganda: A point prevalence survey - Mark Kizito; Darius Owachi; Falisy Lule; Laura Jung; Vivian Bazanye; Ibrahim Mugerwa; Susan Nabadda; Charles Kabugo (PLoS ONE, 2025)
Introduction Effective antimicrobial stewardship programs require data on antimicrobial consumption (AMC) and utilization (AMU) to guide interventions. However, such data is often scarce in low-resource settings. We describe the consumption and utilization of antibiotics at a large tertiary-level hospital in Uganda. Methods In this cross-sectional study at Kiruddu National Referral Hospital, we analyzed medicine delivery records for the period July 2021 to June 2022, accessed on 12/08/2022, to extract AMC data expressed as defined daily doses (DDDs) per 1000 inhabitants per day (DID). We used the WHO point prevalence survey (PPS) to analyze AMU data with a systematic sampling of outpatient department (OPD) for a period between June and August 2022 and selected all inpatient department (IPD) patients admitted before 8:00 AM on 27/11/2022. AMU data was analyzed as the proportion of individual antibiotic prescriptions, indications for prescriptions, and compliance with the national treatment guidelines. Both AMC and AMU data were categorized by the WHO AWaRe (access, watch, and reserve) criteria. Results In the year 2021–2022, a total of 6.05 DID of antibiotics were consumed comprising 3.61 DID (59.6%) access, 2.44 DID (40.3%) watch, and 0.003 (0.1%) reserve antibiotics. The most consumed antibiotics comprised penicillin (1.61 DID, 26.7%), cephalosporins (1.51, 25%), and imidazole (1.10 DID, 18.1%). A total of 119/211 (56%) patients in the OPD and 99/172 (57.5%) patients in the IPD were prescribed antibiotics. Of the 158 OPD antibiotic prescriptions, 73 (46.2%) were access, 72 (45.6%) were watch, 0 (0%) were reserve, and 13 (8.2%) were unclassified antibiotics. Of the 162 IPD antibiotic prescriptions, 62 (38.3%) were access, 88 (54.3%) were watch, 01 (0.6%) was reserve, and 11 (6.8%) were unclassified antibiotics. Indications for antibiotic prescriptions in the OPD comprised respiratory tract infections (53, 38.1%), urinary tract infections (34, 26.6%), gastrointestinal infections (20, 14.4%), sepsis (17, 12.2%), and medical prophylaxis (12, 8.7%). The indications for antibiotic prescriptions in the IPD comprised sepsis (28.2%), respiratory tract infections (18.3%), burn wounds (14.1%), and gastrointestinal infections (14.1%). Conclusion Prescription of watch antibiotics in both OPD and IPD hospital settings was high. Establishment of robust antimicrobial stewardship measures could help improve the rational prescription of antibiotics.